2022
DOI: 10.3390/antibiotics11091173
|View full text |Cite
|
Sign up to set email alerts
|

Buffering Capacity and Effects of Sodium Hexametaphosphate Nanoparticles and Fluoride on the Inorganic Components of Cariogenic-Related Biofilms In Vitro

Abstract: Despite the remarkable effects of sodium hexametaphosphate nanoparticles (HMPnano) on dental enamel de-/re-mineralization processes, information on the effects of these nanoparticles on biofilms is scarce. This study assessed the effects of HMPnano, with or without fluoride (F), on the inorganic components and pH of Streptococcus mutans and Candida albicans dual-species biofilms. Solutions containing conventional/micro-sized HMP (HMPmicro) or HMPnano were prepared at 0.5% and 1%, with or without 1100 ppm F. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…Interestingly, the reduction in the TMP particle size led to an additive effect on the pH of the biofilms as even after sucrose exposure, the biofilms treated with 1TMPn and 3TMPn, combined with F, had significantly higher pH than those treated with their microparticulate counterparts and the positive control (1100 ppm F). In fact, such data are in line with those in literature for another phosphate, which demonstrated that the reduction of sodium hexametaphosphate particle size enhanced its buffering capacity [ 29 ]. Such a trend can also be justified by the higher reactivity of nanoparticles over the microparticles, leading to the enhancement of the effects observed for the groups treated with the conventional particles [ 22 , 23 ].…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, the reduction in the TMP particle size led to an additive effect on the pH of the biofilms as even after sucrose exposure, the biofilms treated with 1TMPn and 3TMPn, combined with F, had significantly higher pH than those treated with their microparticulate counterparts and the positive control (1100 ppm F). In fact, such data are in line with those in literature for another phosphate, which demonstrated that the reduction of sodium hexametaphosphate particle size enhanced its buffering capacity [ 29 ]. Such a trend can also be justified by the higher reactivity of nanoparticles over the microparticles, leading to the enhancement of the effects observed for the groups treated with the conventional particles [ 22 , 23 ].…”
Section: Discussionsupporting
confidence: 91%